Syntactic consructions with comparative forms in the scientific style of the Belarusian literary language of 1920–30s - Naurotskaya, Irina V. (Journal of the Belarusian State University. Philology, 2019)
The paper presents the classification of comparative constructions meanings, quantitative analysis of each kind of constructions was conducted including characterization by sub-styles of the scientific style, the role of constructions with comparative in scientific functional variation was described. This allows to present the Belarusian literary language of 1920–30s as stylistically more well-developed in contrast to the language of the previous period of the newspaper «Nasha Niva», in which only popular scientific prose style was defined, and to conclude that the category of the degrees of comparison realize stylistic purposes of a statement. The category of the degrees of comparison can be considered as a grammatical and functional semantic-stylistic category. It is significant that the stylistic belonging of the primary sources used during the research should be taken into account the classification of language structures. The study identifies certain trends of the Belarusian literary language of 1920–30s. After 1930, refocusing in the formally non correlated superlative forms has been observed. After 1933, limited set of pronouns clarifying the comparatives form or the referred noun is noted. The paper explaines that in the scientific style the method of gradable comparing for description of research activities is the most appropriate compared to the method of opposite contrasting because the object is described in comprehensive review taking into account small specific details with regard to using constructions with comparative forms. The emphasis is placed on the need of a systematic and holistic approach to the study of adjective and adverb comparatives in the Belarusian linguistics.
Keywords: Belarusian literary language of 1920–30s; historical linguistics; scientific style; comparative; comparative degree; elative; superlative; stylistics comparison